MMS observations of oblique small‐scale magnetopause flux ropes near the ion diffusion region during weak guide‐field reconnection - W.‐L. Teh; R. E. Denton; B. U. Ö. Sonnerup; C. Pollock (Geophysical Research Letters)
Abstract We report Magnetospheric Multiscale observations of a series of five small‐scale magnetic flux ropes (FR1–5) embedded in the southward reconnection outflow during a magnetopause reconnection event with a small guide field (~2.2 nT). These small‐scale flux ropes (diameter ~3–11 ion inertial lengths) are found inside or near the ion diffusion region on the magnetosheath side of the magnetopause boundary layer. A consistent result for determining the axis orientation of the flux ropes is achieved using two different methods, namely, minimum variance analysis of the axial electric field and constrained minimum variance analysis of the magnetic field. Our results show that the axes of these flux ropes (FR1–4) form a large angle (53°−66°) to the guide‐field orientation and are tilted toward the direction of the reconnecting field. These observations provide evidence for the presence of oblique ion‐scale flux ropes near the ion diffusion region during reconnection with a weak guide field. Our findings are similar to those obtained from a 3‐D kinetic simulation of turbulent reconnection.